THERMOPLASTIC STRESS ANALYSIS OF GRAPHITE REINFORCED COMPOSITE CANTILEVER BEAM OF ARBITRARY ORIENTATION, SUBJECTED TO UNIFORMLY DISTRIBUTED LOADS - Okumus, Fuat; Turgut, Aydin; Sancaktar, Erol (American Society of Mechanical Engineers (ASME), 2000)
In this study, an elastic-plastic stress analysis is performed in a carbon fiber reinforced thermoplastic composite beam, which is loaded uniformly at the upper surface. An analytical solution is obtained including both the governing differential equations and boundary conditions. The composite beam is loaded uniformly at the upper surface, therefore the normal stress component ?y is neglected in comparison with other stress components. The orientation angle of the composite is changed as 0°, 15°, 30° and 45°. The intensity of the residual stress component of ?x is maximum at the upper and lower surfaces of the composite beam. The intensity of the residual stress component of the shear stress ?xy is maximum around the central axis for the beam. Copyright © 2000 by ASME.
ASME 2000 International Design Engineering Technical Conferences and Computers and Information in Engineering Conference, IDETC-CIE 2000 -- 10 September 2000 through 13 September 2000 -- Baltimore -- 186543
Keywords: Boundary conditions; Elastoplasticity; Reinforced plastics; Shear stress; Stress analysis; A-carbon; Arbitrary orientation; Composite beam; Composite cantilever beams; Distributed loads; Elastic-plastic stress analysis; Reinforced composites; Stress component; Stresses analysis; Upper surface; Residual stresses